Metabolomic Alterations in the Digestive System of the Mantis Shrimp Oratosquilla oratoria Following Short-Term Exposure to Cadmium - Xu, Yingjiang; Liu, Huan; Han, Dianfeng; Ren, Lihua; Gong, Xianghong; Jiang, Fang; Cui, Yanmei; Liu, Xiaojing; Ren, Chuanbo; Xue, Jinglin; Tian, Xiuhui (Frontiers in Physiology, 2021)
Mantis shrimp Oratosquilla oratoria is an economically critical aquatic species along the coast of China but strongly accumulates marine pollutant cadmium in its digestive system. It is necessary to characterize the toxicity of Cd in the digestive system of mantis shrimp. The metabolic process is an essential target of Cd toxicity response. In this work, we used ultra-performance liquid chromatography coupled with time-of-flight mass spectrometry for untargeted metabolomics to characterize the metabolic changes in the digestive system of O. oratoria, exposed to 0.05 mg/L for 96 h. The aim of this study was to further investigate the effect of O. oratoria on Cd response to toxicity and develop biomarkers. Metabolomics analysis showed the alteration of metabolism in the digestive system of mantis shrimp under Cd stress. A total of 91 metabolites were differentially expressed and their main functions were classified into amino acids, phospholipids, and fatty acid esters. The enrichment results of differential metabolite functional pathways showed that biological processes such as amino acid metabolism, transmembrane transport, energy metabolism, and signal transduction are significantly affected. Based on the above results, the Cd-induced oxidative stress and energy metabolism disorders were characterized by the differential expression of amino acids and ADP in mantis shrimp, while the interference of transmembrane transport and signal transduction was due to the differential expression of phospholipids. Overall, this work initially discussed the toxicological response of Cd stress to O. oratoria from the metabolic level and provided new insights into the mechanism.